Anti-aflatoxigenic effect of organic acids produced by Lactobacillus plantarum - Guimarães, Ana Cristina Silva Esperança (2018)
Lactic acid bacteria (LAB), which are commonly used in the production of fermented foods, have been gaining attention for their antifungal and antimycotoxin properties. In this work, the strain Lactobacillus plantarum UM55 was selected among other LAB for inhibiting the growth of Aspergillus flavus. Further, it is shown that cell-free supernatant (CFS) of this strain inhibits the production of aflatoxins (AFLs) by 91%. This inhibition was dependent on CFS pH, increased with increasing concentrations of CFS, and was independent of fungal growth, which was inhibited only by 32%. CFS was also effective in inhibiting the growth and AFLs production in A. parasiticus, A. arachidicola, A. nomius and A. minisclerotigenes. Further, L. plantarum UM55 CFS was analysed for the presence of organic acids and the main differences compared to controls were found in the levels of lactic acid, phenyllactic acid (PLA), hydroxyphenyllactic acid (OH-PLA), and indole lactic acid (ILA). These compounds were individually tested against A. flavus, with all of the compounds showing an inhibiting effect on fungal growth and AFLs production. PLA showed the stronger effects, and the obtained IC90 for the inhibition of growth and AFLs was of 11.9 and 0.87 mg/mL, respectively. AFLs IC90 for ILA, OH-PLA and lactic acid were of 1.47, 1.80, and 3.92 mg/mL, respectively. The antiaflatoxigenic properties of LAB depend on strain's capability to produce lactic acid, PLA, OH-PLA and ILA.